Study of science students’ expectation for university writing courses - Nadarajan, Shanthi (Issues in Language Studies, 2013)
The New Malaysia Education Blueprint (2012) states that the private sector continues to have concerns for Malaysian graduates’ English proficiency. The present study investigates the views and expectations of science students taking English courses in a public university. The findings revealed that learners saw opportunities to communicate and job applications process as important soft skills. They preferred practical learning methods above traditional teaching methods. Learners considered group performance, personal attitudes and online activities as important learning opportunities, while factual knowledge, report writing were least supported despite the fact that the majority viewed both assessments and instructional process as relevant. The data revealed that though they were dissatisfied with their existing level of proficiency, many students continued to expect an A for their course. An assessment of the learner’s’ language ability revealed that language ability was less under the learner’s control and more dependent on learner proficiency level. Taken together, this study suggests that the curriculum for the Professional Writing course should be highly diversified and balanced, with some emphasis on getting less proficient learners to read and improve their grammar skills while better students should be given opportunities to develop creative talents and interpersonal skills.